Anaphylactic Reactions to Blood Transfusion in a Patient with Iron Deficiency Anemia: A Case Report - Shadma H. Quazi1 , Sharjeel H. Khan2 , Sushil K. Varma3 , Shailesh Nagpure4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Obstacles of transfusion of blood are uncommon but can endanger the health. Anaphylactic reactionsassociated with the blood transfusion (BT) of PRC blood components presents as bradycardia followed bytachycardia and urticaria within 15 minutes of transfusion. In suchcases, clinicians should strictly monitorthe patient’s condition at least while the patient receives blood transfusion.Here we are reporting a case of 28 year old pregnant female presented with Iron deficiency anemia (IDA), aLSCS (caesarean section) delivery was performed and blood was transfused, who was affected by an acuteanaphylactic reaction following red cell transfusion. This case highpoints the need to examine potential riskof transfusion of the blood component against the alleged advantage.